Music Therapy and its Impact on Health among Children - Nirmali Gogoi; Sumi Das (Current Approaches in Science and Technology Research Vol. 14, 2021)
Music is one of the few activities that involve using the whole brain. It is intrinsic to all cultures and can have surprising benefits not only for learning language, improving memory and focusing attention, but also for physical coordination and development. It is also effective therapy for pain, reducing blood pressure, medicine for the heart, stroke, alzheimer, autism, speeds post-stroke recovery, chronic headaches & migraine remedy. Music boosts immunity, enhances intelligence, learning and IQ. Music improves concentration, athletic performance, body movement and coordination, productivity, fatigue fighter, mood and decreases depression. Relaxing music induces sleep and reduces stress and aids relaxation. Listening to music helps control negative aspects of our personalities like worry, bias and anger. Of course, music can be distracting if it’s too loud or too jarring, or if it competes for our attention with what we’re trying to do. But for the most part, exposure to many kinds of music has beneficial effects.